Implikasi Hukum Hambatan Pengosongan Objek Hak Tanggungan terhadap Kepastian Hukum Pemenang Lelang yang Beritikad Baik - Ari Surya Kusuma; Itok Dwi Kurniawan; Heri Hartanto (SENTRI: Jurnal Riset Ilmiah, 2025)
The execution of mortgage rights through auction mechanisms should ideally provide legal protection and certainty for creditors and auction winners acting in good faith. However, in practice, the process of vacating the collateral object after the auction often faces legal and non-legal obstacles that prevent the auction winner from immediately taking physical possession of the object, even though ownership rights have been legally transferred through the auction minutes. This study aims to analyze the legal implications of these obstacles to eviction on the legal certainty of auction winners. The research uses a normative legal method with a legislative approach and a case approach through analysis of the Mortgage Law, SEMA, Minister of Finance Regulations, and court decisions. The results of the study show that the Mortgage Law does not explicitly regulate the mechanism for vacating the object after the auction, thus creating a normative vacuum and differences in interpretation in practice. Meanwhile, SEMA Number 4 of 2014 functions as a policy regulation and does not have substantive binding force. As a result, auction winners often experience delays in physical possession, cost losses, and legal uncertainty. This study concludes that regulatory updates are needed regarding the post-auction eviction mechanism, strengthening the authority of the implementing agency, and harmonizing procedural law so that protection and legal certainty for auction winners acting in good faith can be effectively realized.